2007
DOI: 10.1038/sj.embor.7401137
|View full text |Cite
|
Sign up to set email alerts
|

Ku recruits XLF to DNA double‐strand breaks

Abstract: XRCC4-like factor (XLF)-also known as Cernunnos-has recently been shown to be involved in non-homologous end-joining (NHEJ), which is the main pathway for the repair of DNA double-strand breaks (DSBs) in mammalian cells. XLF is likely to enhance NHEJ by stimulating XRCC4-ligase IV-mediated joining of DSBs. Here, we report mechanistic details of XLF recruitment to DSBs. Live cell imaging combined with laser micro-irradiation showed that XLF is an early responder to DSBs and that Ku is essential for XLF recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
165
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 25 publications
15
165
0
1
Order By: Relevance
“…Previously, live cell imaging studies had shown that the recruitment of XLF to DSBs is dependent upon Ku but not XRCC4 (27). Similarly, we found that the recruitment of Nej1 to an in vivo site-specific DSB measured by ChIP was dependent upon yKu but not Lif1 or Dnl4.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previously, live cell imaging studies had shown that the recruitment of XLF to DSBs is dependent upon Ku but not XRCC4 (27). Similarly, we found that the recruitment of Nej1 to an in vivo site-specific DSB measured by ChIP was dependent upon yKu but not Lif1 or Dnl4.…”
Section: Discussionsupporting
confidence: 58%
“…This notion is supported by parallel studies with the mammalian ortholog of Nej1, XLF (XRCC4-like factor; Cernunnos) (25)(26)(27). Notably, XLF not only stimulates the joining of cohesive DNA ends by DNA ligase IV-XRCC4 but also the joining of mismatched DNA ends (28 -34).…”
supporting
confidence: 56%
“…Previous NHEJ models suggested that after binding of Ku to DNA ends, DNA-PKcs binds Ku:DNA to form a DNA-PK holoenzyme and bridges the broken ends (15)(16)(17)(18); however, recent experiments indicate that DNAPKcs may have different roles in NHEJ, such as the stabilization of core NHEJ factors, recruitment and retention of accessory factors, involvement in the DDR signaling cascade, and repair of complex and clustered DSBs (19)(20)(21)(22)(23)(24)(25). In addition, recent structural studies have shown that XRCC4 and XLF form filamentous structures in vitro (26)(27)(28).…”
mentioning
confidence: 99%
“…The latter steps of NHEJ require additional proteins, including Artemis (endprocessing nuclease), XLF/Cerrunos, and the XRCC4/ligIV complex (ligase) (Jackson and Bartek 2009). More recent data on NHEJ assembly during DNA repair argue for a more complex model in which cooperative interactions between various NHEJ components orchestrate a precise architecture (Yano et al 2008). It has been shown that DNA-PK is autophosphorylated on DNA-PKcs at multiple residues, and such autophosphorylation is important for the completion of DNA repair (Meek et al 2008).…”
mentioning
confidence: 99%